Gene expression profiles of breast cancer metastasis according to organ site. Issue 1 (23rd June 2021) - Brasó‐Maristany, Fara; Paré, Laia; Chic, Nuria; Martínez‐Sáez, Olga; Pascual, Tomás; Mallafré‐Larrosa, Meritxell; Schettini, Francesco; González‐Farré, Blanca; Sanfeliu, Esther; Martínez, Débora; Galván, Patricia; Barnadas, Esther; et al.
Abstract : In advanced breast cancer, biomarker identification and patient selection using a metastatic tumor biopsy is becoming more necessary. However, the biology of metastasis according to the organ site is largely unknown. Here, we evaluated the expression of 771 genes in 184 metastatic samples across 11 organs, including liver, lung, brain, and bone, and made the following observations. First, all PAM50 molecular intrinsic subtypes were represented across organs and within immunohistochemistry‐based groups. Second, HER2‐low disease was identified across all organ sites, including bone, and HER2 expression significantly correlated with ERBB2 expression. Third, the majority of expression variation was explained by intrinsic subtype and not organ of metastasis. Fourth, subtypes and individual subtype‐related genes/signatures were significantly associated with overall survival. Fifth, we identified 74 genes whose expression was organ‐specific and subtype‐independent. Finally, immune profiles were found more expressed in lung compared to brain or liver metastasis. Our results suggest that relevant tumor biology can be captured in metastatic tissues across a variety of organ sites; however, unique biological features according to organ site were also identified and future studies should explore their implications in diagnostic and therapeutic interventions. Abstract : We evaluated gene expression in 184 metastatic breast cancer samples across 11 organs. All PAM50 subtypes were represented across metastatic sites and associated with survival. HER2‐low disease was identified across sites. Immune gene expression was higher in lung than brain or liver metastasis. Relevant tumor biology can be captured in metastatic tissue, while each site shows unique biological features.